1989
DOI: 10.1104/pp.89.4.1401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Plasma Membrane and Tonoplast ATPases of Barley Roots

Abstract: The effect of temperature on the rate of proton transport and ATP hydrolysis by plasma membrane (PM) and tonoplast (TN) ATPases from barley (Hordeum vulgare L. cv CM 72) roots were compared. Rates of proton transport were estimated using the fluorescent amine dyes quinacrine and acridine orange. The ratio between rate of transport and ATP hydrolysis was found to depend on the dye, the temperature, and the type of membrane. The PM ATPase had an estimated Arrhenius energy of activation (Ea) of approximately 18 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…The temperature optimum for ATP hydrolysis for maize root vanadate-sensitive proton pump was found above 40°C ( Figs. 1 and 2), which is similar to that reported previously (6,7,10,15,20). Therefore, proton transport and ATP hydrolysis by the maize root plasma membrane-type proton pump had different temperature optima.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The temperature optimum for ATP hydrolysis for maize root vanadate-sensitive proton pump was found above 40°C ( Figs. 1 and 2), which is similar to that reported previously (6,7,10,15,20). Therefore, proton transport and ATP hydrolysis by the maize root plasma membrane-type proton pump had different temperature optima.…”
Section: Discussionsupporting
confidence: 77%
“…m *RATP, is equal to the magnitude ofthe inhibitory processes, kp,. 6. In addition, the time course for the generation of the proton gradient can be reproduced by knowing two of the following three parameters: RH, A, and kp.…”
Section: Materials and Methods Preparation Of Membrane Vesiclesmentioning
confidence: 99%
“…Microsomal membranes were prepared, separated on linear or discontinuous sucrose gradients, and fractions were collected as described previously (13)(14)(15). TN was collected from the 22/30% sucrose interface and PM was collected from the 34/40% sucrose interface.…”
Section: Membrane Preparationmentioning
confidence: 99%
“…It has been suggested that both types oftransporter may exist in a single membrane type (2, 30) although this has not been investigated in higher plants. We examined the Ca2+-transport activity of microsomes isolated from barley roots in order to determine which ofthe two types ofCa2+ transporters were associated with the major organelle fractions.The mechanisms by which Ca2+ is transported out of the cytoplasm against a large concentration gradient can be studied using isolated membrane vesicles (3,6,7,11,17,22,28,31,32 (13)(14)(15)(16). In the present paper the mechanisms and capacity for formation of Ca2`gradients by these vesicles are assessed.…”
mentioning
confidence: 99%
See 1 more Smart Citation